2018
DOI: 10.3389/fimmu.2018.01788
|View full text |Cite
|
Sign up to set email alerts
|

The p.Arg435His Variation of IgG3 With High Affinity to FcRn Is Associated With Susceptibility for Pemphigus Vulgaris—Analysis of Four Different Ethnic Cohorts

Abstract: IgG3 is the IgG subclass with the strongest effector functions among all four IgG subclasses and the highest degree of allelic variability among all constant immunoglobulin genes. Due to its genetic position, IgG3 is often the first isotype an antibody switches to before IgG1 or IgG4. Compared with the other IgG subclasses, it has a reduced half-life which is probably connected to a decreased affinity to the neonatal Fc receptor (FcRn). However, a few allelic variants harbor an amino acid replacement of His435… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Overexpression of ST18 is able to heighten the susceptibility to deletion of keratinocytes adhesion, and enhanced extracellular signal-regulated kinase (ERK) signaling is a possible mechanism [ 16 ]. A p.Arg435His variation in IgG3 has been reported to be associated with PV in cohorts including German, Turkish, Egyptian and Iranian patients [ 17 ].…”
Section: Pemphigusmentioning
confidence: 99%
“…Overexpression of ST18 is able to heighten the susceptibility to deletion of keratinocytes adhesion, and enhanced extracellular signal-regulated kinase (ERK) signaling is a possible mechanism [ 16 ]. A p.Arg435His variation in IgG3 has been reported to be associated with PV in cohorts including German, Turkish, Egyptian and Iranian patients [ 17 ].…”
Section: Pemphigusmentioning
confidence: 99%
“…In this study, blocking of FcRn abolished the capacity of PV sera to cause detachment of keratinocytes in vitro (284). In another study, Recke et al (285) found that an allelic variant harboring an amino acid replacement of His435 to Arg favoring high affinity of IgG3 to FcRn was associated with an increase risk of PV. Altogether these studies raise evidence for a potential benefit of targeting FcRn in pemphigus.…”
Section: Emerging Therapiesmentioning
confidence: 99%
“…The H435-IgG3 allele is most common in Africans (30%-60%), suggesting a possible role for positive selection, given its relatively high frequency in malaria endemic areas [9]. However, the G3m15 and G3m16 allotypes have also been associated with increased susceptibility to the autoantibody-mediated disease pemphigus vulgaris (PV), a severe blistering skin disorder, and thus, IgG3 might play a role in the pathogenesis of PV; alternatively, there may be a genetic association between H435-IgG3 alleles and PV in Middle Eastern and North African countries [101]. More research on IgG3 polymorphism frequencies in endemic populations may aid in the identification of potential selective advantages and disadvantages of these IgG3 polymorphisms [9].…”
Section: Parasitic Infectionsmentioning
confidence: 99%